Numerical simulation of flow and mixing processes within cylindrical stabiliser burner - Фиалко, Наталия Михайловна; Шеренковский, Юлий Владиславович; Майсон, Николай Владимирович; Меранова, Наталья Олеговна; Абдулин, Михаил Загретдинович; Бутовский, Леонид Сергеевич; Полозенко, Нина Петровна; Клищ, Андрей Владимирович; Стрижеус, Светлана Николаевна; Тимощенко, Александра Борисовна (Eastern-European Journal of Enterprise Technologies, 2014)
A complex of numerical simulation on determining the patterns of the influence of various ways of transfer processes intensification in cylindrical stabilizer burners with fuel feed by introducing in the cross flow of oxidant on the characteristics of these processes is performed. The studies of the influence of a rectangular annular recess on the flow parameters in cylindrical burner are conducted. It is found that, in the presence of recess, the flow turbulence intensity increases. Moreover, at places of its maximum values it may almost twice exceed the corresponding quantities in the absence of recess. Zone of the greatest influence of the recess on the flow turbulization is localized near its position, which is important for fuel ignition and flame stabilization. Pressure losses, associated with the presence of the annular rectangular recess are small and, for the considered conditions, do not exceed 6% of the total pressure losses in the burner in the absence of recess. The analysis of opportunities of flow and mixing intensification in cylindrical burners by mounting plate flow turbulators on stalling edges of the stabilizer is carried out. It is shown that using turbulators provides significant flow turbulization, which is to the greatest extent apparent near the boundaries of recirculation mixing zones. This is accompanied by mixing processes intensification in accordance with fuel and oxidant flow turbulization.